Consolidating Indonesiaâ€™s Fragile Elections Through E-Voting: Lessons Learned from India and the Philippines - Elven, Tareq Muhammad Aziz; Al-Muqorrobin, Shalahuddin Ahmad (Indonesian Comparative Law Review, 2020)
This research argues that implementing the electronic voting (e-voting) system in Indonesia is urged following the nation's first-ever 2019 simultaneous elections, which cost a deadly price of 527 election official lives of reported extreme fatigue during and after the event. Billed as "the world's most complex election", it has reached a consensus that the current manual election system, in which five different paper-based elections are voted at a time, has to be changed. Not to mention that the long-time gap between the voting day and the result announcement may create an opportunity for election fraud. This is evidenced by loads of electoral dispute lawsuits from the previous election brought to the Constitutional Court of Indonesia accused the others of cheating. This research stresses that despite the controversies of whether Indonesia, an archipelagic country with more than 17 thousand islands and 267 million people, is ready for e-voting.Â  Whether the application of technology is an appropriate response to the election problems? E-voting is desired as a long-term solution and intends to solve many issues such as speeding the counting of ballots, reducing the cost of elections, providing accessibility for disabled voters, and increasing overall voter turnout.